PENGEMBANGAN MEDIA KELAS VIRTUAL BERBASIS BLOGSPOT DALAM PEMBELAJARAN MEMBACA CERPEN BAGI SISWA KELAS IX (SATU Press Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2021)
Learning of reading short stories currently requires media that are in accordance with technological developments. In addition with distance learning because of the Covid-19 pandemic, learning media is needed that supports the target of reading short stories learning. Therefore, this research develops a learning media called Virtual Class. This research aims to (1) develop a learning media called Virtual Class in learning of reading short stories; (2) describe the results of the effectiveness trial of using Virtual Class media in learning of reading short stories for IX grade. This research uses a development method that adapts the waterfall model. The development procedure begins with needs analysis, design, testing, and usage. Data collection techniques used in this research are observation and interview techniques. Data are analyzed using interactive techniques. The results of the research indicate that the Virtual Class media is an effective learning media in learning of reading short stories. In addition, the Virtual Class media contains content/material, a clear display presentation, and practice questions. So, Virtual Class media can be used as an alternative media for learning of reading short stories for grades IX via online. According to media experts, there are several things that must be improved from this media, including (a) improving greetings in the introduction to learning; (b) improve the use of language again because there are still errors in writing capital letters in the material on the blog; (3) the material should be added with examples.